2022
DOI: 10.1002/alr.23047
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐controlled radiofrequency neurolysis for treatment of chronic rhinitis: 12‐month outcomes after treatment in a randomized controlled trial

Abstract: Background Temperature‐controlled radiofrequency (TCRF) neurolysis of the posterior nasal nerve (PNN) area for the treatment of chronic rhinitis was previously reported as superior to a sham‐control procedure at 3 months postprocedure in a randomized controlled trial (RCT). The primary endpoint was a responder rate of ≥30% improvement (decrease) for 24‐hour reflective total nasal symptom score (rTNSS) compared with baseline. Herein, 12‐month outcomes after active treatment are reported. Methods In this prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…Allergic, non-allergic, and mixed subtypes of rhinitis were all included, but seasonal allergies were excluded in three studies. [7][8][9] Patients with altered anatomy of the posterior nose as a result of prior sinus or nasal surgery/injury or who had prior procedure/surgery for chronic rhinitis were excluded in three of the studies. [7][8][9] All five studies were pragmatic in their design, which meant that concomitant medications for chronic rhinitis were not discontinued or controlled for.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Allergic, non-allergic, and mixed subtypes of rhinitis were all included, but seasonal allergies were excluded in three studies. [7][8][9] Patients with altered anatomy of the posterior nose as a result of prior sinus or nasal surgery/injury or who had prior procedure/surgery for chronic rhinitis were excluded in three of the studies. [7][8][9] All five studies were pragmatic in their design, which meant that concomitant medications for chronic rhinitis were not discontinued or controlled for.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
“…8 Postnasal drip and cough scores were measured in four out of the five studies, where these symptoms also improved significantly from baseline to each follow up time point (Table II). 7,[9][10][11] Quality of Life (QoL) Measures Two studies evaluated patient QoL outcomes, and both showed an overall improvement in QoL with treatment. 7,11 Lee 2022 used the mini-RQLQ, which is a validated questionnaire that consists of 14 questions in five domains (activity limitations, practical problems, nose symptoms, eye symptoms, and other symptoms), with a maximum score of 14 points.…”
Section: Rtnss Subscores Postnasal Drip and Cough Scoresmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on surgical interventions for rhinitis have shown success with posterior nasal nerve (PNN) cryoablation, 3 radiofrequency, 4 or endoscopic posterior nasal neurectomy (EPNN) 2,3 . These interventions remove postganglionic parasympathetic nasal innervation, which helps avoid endoscopic vidian neurectomy (EVN)‐related complications like xerophthalmia and facial/palatal hypesthesia 3,5 …”
Section: Introductionmentioning
confidence: 99%